Late Pleistocene and Holocene glaciation and deglaciation of Melville Peninsula, Northern Laurentide Ice Sheet - Dredge, Lynda (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2001)
AbstractMelville Peninsula lies within the Foxe/Baffin Sector of the Laurentide Ice Sheet. Pre-Foxe/Pre-Wisconsin ice may have covered the entire peninsula. Preserved regolith in uplands indicates a subsequent weathering interval. Striations and till types indicate that, during the last (Foxe) glaciation, a local ice sheet (Melville Ice) initially developed on plateaus, but was later subsumed by the regional Foxe ice sheet. Ice from the central Foxe dome flowed across northern areas and Rae Isthmus, while ice from a subsidiary divide controlled flow on southern uplands. Ice remained cold-based and non-erosive on some plateaus, but changed from cold- to warm-based under other parts of the subsidiary ice divide, and was warm-based elsewhere. Ice streaming, generating carbonate till plumes, was prevalent during deglaciation. A late, quartzite-bearing southwestward ice flow from Baffin Island crossed onto the north coast. A marine incursion began in Committee Bay about 14 ka and advanced southwards to Wales Island by 8.6 ka. The marine-based ice centre in Foxe Basin broke up about 6.9 ka. Northern Melville Peninsula and Rae Isthmus were deglaciated rapidly, but remnant ice caps remained active and advanced into some areas. The ice caps began to retreat from coastal areas ~6.4 to 6.1 ka, by which time sea level had fallen from 150-180 m to 100 m.